Effect of 808nm diode laser irradiation on root canal walls after smear layer removal: A scanning electron microscope study - Parirokh, Masoud; Eghbal, Mohammad Jafar; Asgary, Saeed; Ghoddusi, Jamileh; Stowe, Sally; Forghani, Farshid; hahravan, Arash (Iranian Endodontic Journal, 2008)
Introduction: This study was carried out to investigate the effect of 808nm diode laser irradiation on dentinal tubules of root canal wall. Materials and Methods: Twelve single-rooted teeth were used. After cleaning and shaping with rotary instruments by the crown down technique, the smear layer was removed by alternating irrigation with EDTA and sodium hypochlorite. The teeth were then randomly divided into experimental and control groups of six teeth each. In experimental group, laser irradiation was activated inside the canal and the teeth of the other group served as controls. Kruskal-Wallis and Friedman tests were used for comparing occluded dentinal tubules in different part of the roots. Results: Scanning electron microscopy showed that occluded dentinal tubules could be observed in all laser irradiated teeth; however, none of the control teeth showed occluded dentinal tubules. The Friedman test showed that in the laser irradiated group the best result was achieved in the apical third of the root canals compared with the middle (p<0.005) and cervical third (p<0.002). Dentinal tubules of the middle third were also significantly different from the cervical third as well (p<0.005). Conclusion: Laser radiation after removing smear layer could successfully occlude dentinal tubules and the best results was achieved at the apical part of the canal.